Pengaruh Motivasi Dan Komitmen Organisasi Terhadap Kinerja Pengurus Pondok Pesantren Bahrul Ulum (Induk) Tambakberas Jombang - Ansori, Ahmad Zakaria; Mahendri, Wisnu (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2022)
This study aims to determine the effect of motivation and organizational commitment simultaneously on the performance of the management. This research uses a quantitative approach with an associative type, which is a research plan that states the relationship between two or more variables by collecting data that is numbered and then processed with certain statistical formulas, so that information about the variables studied is obtained. The population in this study was to find 100 people while the sample found 80 people who were administrators of the bahrul ulum Islamic boarding school (parent) of Jombang rice ponds. Data were collected using the questionnaire method, which was then analyzed by multiple regression analysis using SPSS version 26. The results showed that partially the motivational variable had a positive but not significant effect on performance, while the organizational commitment variable had a positive and significant effect. Simultaneously, the variables of motivation and organizational commitment have an effect on the performance of the management of the boarding school in Bahrul Ulum Tambakberas Jombang. The results of the analysis of the coefficient of determination obtained are 0.151 or 15.1%, which means that the contribution of motivation and organizational commitment variables is 15.1%, while the influence of other factors outside this regression model.